Onset of calciotropic receptors during the initiation of mandibular/alveolar bone formation - Bobek, Jan; Oralová, Veronika; Lesot, Herve; Kratochvílová, Adéla; Doubek, Jaroslav; Matalova, Eva (Annals of anatomy, 2020)
Mandibular/alveolar (m/a) bone, as a component of the periodontal apparatus, allows for the proper tooth anchorage and function of dentition. Bone formation around the tooth germs starts prenatally and, in the mouse model, the mesenchymal condensation turns into a complex vascularized bone (containing osteo-blasts, -cytes, -clasts) within only two days. This very short but critical period is characterized by synchronized cellular and molecular events. The m/a bone, as others, is subjected to endocrine regulations. This not only requires vasculature to allow the circulation of active molecules (ligands), but also the expression of corresponding cell receptors to define target tissues. This contribution aimed at following the dynamics of calciotropic receptors ́ expression during morphological transformation of a mesenchymal condensation into the initial m/a bone structure. Receptors for all three calciotropic systemic regulators: parathormone, calcitonin and activated vitamin D (calcitriol), were localized on serial histological sections using immunochemistry and their relative expression was quantified by q-PCR. The onset of calciotropic receptors was followed along with bone cell differentiation (as checked using osteocalcin, sclerostin, RANK and TRAP) and vascularization (CD31) during mouse prenatal/embryonic (E) days 13-15 and 18. Additionally, the timing of calciotropic receptor appearance was compared with that of estrogen receptors (ESR1, ESR2). PTH receptor (PTH1r) appeared in the bone already at E13, when the first osteocalcin-positive cells were detected within the mesenchymal condensation forming the bone anlage. At this stage, blood vessels were only lining the condensation. At E14, the osteoblasts started to express the receptor for activated vitamin D (VDR). At this stage, the vasculature just penetrated the forming bone. On the same day, the first TRAP-positive (but not yet multinucleated) osteoclastic cells were identified. However, calcitonin receptor was detected only one day later. The first Sost-positive osteocytes, present at E15, were PTH1r and VDR positive. ESR1 almost copied the expression pattern of PTH1r, and ESR2 appearance was similar with VDR with a significant increase between E15 and E18. This report focuses on the in vivo situation and links morphological transformation of the mesenchymal cell condensation into a bone structure with dynamics of cell differentiation/maturation, vascularization and onset of receptors for calciotropic endocrine signalling in developing m/a bone.
Keywords: Animals; mandibula; Adaptor Proteins, Signal Transducing; osteogeneze; osteoblasty; adaptorové proteiny signální transdukční; Receptors, Calcitonin; Osteoclasts; Immunohistochemistry; buněčná diferenciace; osteokalcin; Mice; Mandible; receptory kalcitoninu; messenger RNA; Osteocalcin; myši; imunohistochemie; osteoklasty; RNA, Messenger; osteocyty; Osteoblasts; Cell Differentiation; Osteogenesis; zvířata; Osteocytes; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction